The effects of blockchain implementation on Cyber risks mitigating strategies in the financial sector in the United Arab Emirates - SAADEH, YASSER MOHAMMED (2018)
Blockchain technology will be the base of current and future business in all fields, as it allows information to be transferred and updated by network participants in a trustworthy, secure and efficient way. This feature and other main success factors of blockchain encourage researchers to concentrate on the chances to benefit from blockchain in the efforts to decrease the effects of cyber threats on the business and improve the cyber defense. Also, to shift from reactive to proactive risk resilience. This study has been devoted to finding out the effects of blockchain implementation on cyber risks mitigating strategies, mainly in the financial sector in the UAE. The study concentrates on the following factors: governance, insider threats, technology and processes. The quantitative method was used by creating an online questionnaire to collect data. Besides that, a hard copy was distributed to get more feedback. Ethical issues were anticipated and considered in this research. A total of 149 completed and accepted responses were received. The statistical package for social sciences (SPSS) was used to analyze the responses by using different analysis techniques like Cronbach’s alpha, correlation test and regression test. The findings show that there is an influence of blockchain implementation factors on cyber risks mitigating strategies. Therefore, the blockchain supports these factors on mitigating the cyber threats and executing proactive steps to avoid any future threats. The paper is limited to evaluate the effect of blockchain implementation on cyber risks mitigating strategies which related to governance, insider threats, technologies and processes. Therefore, further studies are required for better and deeper understanding of the effects of blockchain on insider threats, governance and processes. In addition, it is recommended to extend the study towards the effects of blockchain on other factors of cyber risks. Finally, further studies are required to explore the blockchain implementation in the financial sector.